Community Conversations Shape Reciprocal Partnerships for Social Justice: A Case Study of a Comprehensive Service-Learning Initiative in a Teacher Education Program - Tinkler, Alan; Tinkler, Barri (International Journal of Research on Service-Learning in Teacher Education, 2018)
Our teacher education program pursued a Learn and Serve grant with the goal of integrating service-learning experiences throughout the teacher education course sequence. We approached this work with social justice goals in mind, employing community conversations to ensure a participatory process when working with community partners, and we sought to design and implement experiences that prompted our preservice teachers to think beyond the confines of their own experiences as learners. This case study describes this comprehensive initiative, including the conceptual model we used to frame our work. In addition, we describe the results of research we employed to explore the impact of the initiative on the community and on our students.